2013
DOI: 10.1007/s10661-013-3486-7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting new Buffel grass infestations in Australian arid lands: evaluation of methods using high-resolution multispectral imagery and aerial photography

Abstract: We assess the feasibility of using airborne imagery for Buffel grass detection in Australian arid lands and evaluate four commonly used image classification techniques (visual estimate, manual digitisation, unsupervised classification and normalised difference vegetation index (NDVI) thresholding) for their suitability to this purpose. Colour digital aerial photography captured at approximately 5 cm of ground sample distance (GSD) and four-band (visible–near-infrared) multispectral imagery (25 cm GSD) were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The present study represents a competitive approach for the use of UAVs and machine learning-based classification models compared with alternative solutions. It complements the research outcomes on buffel grass of Marshall et al [ 19 ] by confirming a feasible, accurate, lightweight and relatively cheap solution for invasive grass mapping. With regard to invasive grasses in arid lands, this paper has demonstrated that using only high-resolution RGB images and single pixel-wise classification satisfies the need for accurate and efficient detection and segmentation solutions.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The present study represents a competitive approach for the use of UAVs and machine learning-based classification models compared with alternative solutions. It complements the research outcomes on buffel grass of Marshall et al [ 19 ] by confirming a feasible, accurate, lightweight and relatively cheap solution for invasive grass mapping. With regard to invasive grasses in arid lands, this paper has demonstrated that using only high-resolution RGB images and single pixel-wise classification satisfies the need for accurate and efficient detection and segmentation solutions.…”
Section: Discussionsupporting
confidence: 67%
“…Research from Olsson et al [ 18 ], for instance, demonstrated the importance of using hyperspectral imagery for invasive grass detection as compared with satellite imagery. A feasibility study of sensing technology by Marshall et al [ 19 ], for example, illustrates the potential for regional mapping of buffel grass infestations in arid landscapes using high-resolution aerial photography in red, green, blue (RGB) colour model at a cm/pixel scale over multi- and hyperspectral technologies for overall detection rates.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the latest remote sensing technologies in an innovative way can expand the range of monitoring tools and enhance nature conservation and scientific research efficiency. Demands on the use of high-resolution remote sensing procedures and spatial data in nature conservation projects [9][10][11][12], in environmental and restoration ecology [13][14][15], mapping and monitoring natural phenomena are growing [16][17][18][19]. However, data collection is confronted with the controversial challenges of increasing spatial resolution, higher frequency of surveys, and ever-faster evaluation providing readily available information on increasingly large areas [20][21][22][23][24][25][26][27].…”
Section: Introduction 1motivationsmentioning
confidence: 99%
“…However, VHR data are increasingly proving to be of much use in the process of invasion mapping specifically because of the precision and detail that these data provide in separating signatures of different land cover types. These data have been used largely in temperate regions as well as grasslands to single out invasion by one or two species occurring in homogeneous stands ( Laliberte et al, 2004 ; van Lier et al, 2009 ; Marshall et al, 2014 ). Although VHR data is now widely being used for invasion mapping, many scientists argue that the amount of detail provided by these data may sometimes prove to be too much for easy separation of intended classes ( Nagendra and Rocchini, 2008 ).…”
Section: Introductionmentioning
confidence: 99%